Dinamika Hubungan Pemerintah Pusat dan Daerah dalam Penanganan COVID-19: Studi Kasus di Pemerintah Provinsi DKI Jakarta - Jacko Ryan (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2022)
This research examines the relationship dynamics between the central government and the DKI Jakarta Provincial Government in handling COVID-19 in DKI Jakarta. This research uses a qualitative method with a case study approach. Various research data were collected through interviews with key figures in the central government and DKI Jakarta Provincial Government and literature studies from multiple books, journal scientific articles, and news articles. This research shows that the DKI Jakarta Provincial Government has implemented initiatives and policy innovations for managing COVID-19. However, this caused a reaction from the Central Government. Various causes, such as the lack of regulations, data, and information, differences in perceptions, weak coordination, and the influence of political factors, affect the shift in the form of central-regional government relations from partnership and interaction to the agency. Along with various improvements, especially in terms of drafting regulations and coordination mechanisms, the relationship between the Central Government and the Provincial Government of DKI Jakarta is increasingly showing progress. That is the main asset to creating effective handling of COVID-19 in DKI Jakarta.